Bioactivity of probiotic whey cheese: characterization of the content of peptides and organic acids. (11th February 2013) - Madureira, Ana R; Soares, José C; Amorim, Maria; Tavares, Tânia; Gomes, Ana M; Pintado, Maria M; Malcata, Francisco X
Abstract Background Probiotic whey cheeses have been produced for several years. It is recognized that several bacterium‐mediated metabolic activities contribute differently to the final sensory and nutritional profiles of dairy products. Hence the metabolic activity of probiotic strains in a whey cheese and their contribution to the bioactivity of such matrices were investigated here, including in particular Bifidobacterium animalis, Lactobacillus acidophilus and Lactobacillus casei. Results Both L. casei and B. animalis produce lactic and acetic acids, whereas L. acidophilus produce mainly lactic acid; these metabolites may be considered bioprotection factors. Water‐soluble extracts (WSE) obtained from these cheese matrices were subjected to ultrafiltration through a 3 kDa cut‐off membrane, and the eluted peptides were resolved by high‐performance liquid chromatography. Different qualitative and quantitative profiles were obtained, depending on the strain. WSE were further assayed for their ability to inhibit angiotensin‐converting enzyme; the <3 kDa fraction exhibited higher activities in the case of L. casei and B. animalis than the control and L. acidophilus. Conclusion Whey cheeses with higher nutritional value were those inoculated with L. casei.